Long-term Follow-up of a Phase 2 Clinical Trial to Induce Tolerance in Living Donor Renal Transplant Recipients. (July 2018) - Ildstad, Suzanne; Leventhal, Joseph; Galvin, John; Stare, Dianne; Kurtenbach, K; Ravindra, Kadiyala; Horwitz, M; Abecassis, Michael
Abstract : 37 pts have been transplanted in a phase 2 protocol to induce tolerance in recipients of living donor renal allografts (KTx). The protocol is based upon tolerogenic CD8+/TCR-facilitating cells (FCRx) and nonmyeloablative conditioning. Recipients were conditioned with fludarabine (30mg/m2 days -5, -4, -3), cyclophosphamide (50mg/kg day-3 and+3), 200 cGy TBI (day-1) followed by KTx(day0). A G-CSF mobilized peripheral blood mononuclear cell product was apheresed from the donor >2 weeks pre-KTx, processed to remove graft-versus-host disease (GVHD)-producing cells yet retain CD34 +cells and FC, and cryopreserved until use day+1 post-KTx. 36 pts have reached at least 1 year of FU (range 12-105 months) and are the focus of this analysis. Pts ranged in age from 18-65 yrs. Enrollment was agnostic to degree of HLA match; 2 pts were 6/6 and 3 5/6 related, with the remainder 4/6 to 0/6 matched related (n=15) or unrelated (n=16) Two were re-transplants. Tacrolimus/MMF immunosuppression (IS) was weaned and discontinued at 1 year if chimerism, normal renal fcn and normal KTx biopsy were noted. 34 of 36 exhibited peripheral blood donor chimerism at one month post KTx. Durable chimerism allowing for full IS withdrawal developed in 26(time off IS from 1- 88 months); the majority (23/26)showed full (>95%) donor whole blood/T cell chimerism. Transient chimerism was seen in 8 pts. Durably chimeric pts retained chimerism after removal of IS, remain rejection-free w.o DSA, and show immune competence. Transiently chimeric subjects resumed endogenous hematopoiesis and are maintained on low-dose IS with stable renal fcn. There have been two cases of GVHD: one grade 1-2 acute GI GVHD that responded to steroids; this pt has developed chronic GVHD. The second presented late following development of symptoms and manifested treatment resistant GI GVHD with associated CMV that proved fatal at 11 months post-Tx. There have been two additional graft losses, both previously reported and related to infections. A second subject death occurred in a heavy (>100 pack yr) smoker who developed advanced stage lung cancer 4.5 years after Tx. Overall patient survival is 94.4% and death censored graft survival 94.1%. In summary, high levels of durable chimerism and tolerance with a low (5.5%) incidence of GVHD has been achieved in recipients of FCRx + LDKTx.